The Role of Technology-enhanced Learning (TEL) and eSkills in Higher Education: Challenges, Opportunities, and Future Directions - Israel Creleanor Mulaudzi (E-Journal of Humanities, Arts and Social Sciences)
This article examines the role of Technology-enhanced Learning (TEL) and the development of eSkills in higher education. It delves into how digital tools influence teaching effectiveness, student engagement, and the acquisition of essential skills in a rapidly evolving digital landscape. The study used a mixed-methods approach to collect quantitative data from student surveys and qualitative insights from educator interviews. The analysis revealed that while TEL offers significant opportunities for improving student engagement and skill development, its effectiveness is hampered by several barriers. Key challenges include gaps in digital literacy, inadequate infrastructure, and the persistent digital divide affecting students and educators. The findings underscore the importance of addressing these obstacles to harness TEL’s potential fully. The article recommends targeted interventions to overcome these challenges, including tailored digital literacy training for educators and students, increased investment in digital infrastructure, and the strategic alignment of TEL tools with pedagogical goals. By doing so, higher education institutions can create more inclusive, equitable, and effective learning environments. The research contributes to ongoing discussions on the role of technology in education and provides actionable solutions to promote a more integrated and accessible TEL framework.